Spectral profiles of commercial omega-3 supplements: an exploratory analysis by ATR-FTIR and (1)H NMR - Lopes, Thiago I. B. (J Food Sci Technol, 2019)
Most of the population is dependent on supplemental products to reach the recommended level of omega-3 polyunsaturated fatty acid (ω-3 PUFA) intake. Thus, knowledge about the quality of ω-3 supplements is important for their safe consumption. In this work, attenuated total reflectance–Fourier transform infrared (ATR-FTIR) and nuclear magnetic resonance (NMR) spectroscopy were applied to assess the quality of fourteen commercial ω-3 supplements. Using ATR-FTIR data, we could identify whether ω-3 PUFA was esterified as either triacylglyceride (71%) or ethyl (29%) esters in ω-3 supplements. The type of esterification is rarely included in the product labels, although the consumer should have the right to choose which form of the supplement to consume. On the other hand, (1)H NMR spectra were useful to determine the relative concentration of eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids, and ω-3 PUFA in these commercial samples. Ethyl esters have higher concentrations of unsaturated fatty acids. The NMR results showed a good agreement between the obtained and declared DHA and EPA amounts on the product labels, except for one sample whose high level of ω-3 PUFA indicated it to be a vegetable oil-enriched supplement. Moreover, ω-3 supplements from Schizochytrium sp. microalgae oil revealed higher levels of DHA and ω-3 PUFA, but lower levels of EPA than fish oil. These findings indicate the need for a constant assessment of the quality of commercial products whose ATR-FTIR spectra could be routinely used for the evaluation of PUFA esterification, and NMR analysis could be used to provide advanced quantitative information on commercial ω-3 supplements. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-019-04157-y) contains supplementary material, which is available to authorized users.